Indonesian Teachers' Beliefs and Competencies in Implementing the Indonesian Prototype Curriculum to Promote SDG Goal 4 - Sipayung, Elly Ramadhani; Hsu, Chia-Hua (Educative: Jurnal Ilmiah Pendidikan, 2023)
This qualitative study explores how Indonesian teachers align their beliefs and competencies with curriculum reform, specifically Kurikulum Merdeka and Sustainable Development Goal 4 (SDG 4) - Quality Education. Semi-structured interviews with teachers from elite private and international schools reveal key themes, such as holistic student development, innovative teaching, and curriculum flexibility. ATLAS.ti aids thematic analysis. The study emphasizes the crucial role of external professional support in addressing teachers' mental health challenges and promoting overall well-being. The research provides insights into the complex relationship between teacher beliefs, competencies, and curriculum implementation. It offers valuable perspectives for policymakers, curriculum developers, and educators striving for quality education. The research recognizes potential limitations, including its focus on specific Indonesian teachers and the qualitative nature of the study. Future studies could diversify participants and further explore the impact of teacher well-being on educational practices.